ORGAN-PRESERVING SURGICAL TECHNIQUES AND PROGNOSIS IN PEDIATRIC PATIENTS WITH HEPATIC AND TUMOR PATHOLOGIES (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
This comprehensive analysis examines current organ-sparing methodologies, their impact on prognosis, and emerging technologies in pediatric hepatic surgery. Recent advances in imaging, surgical instrumentation, and perioperative management have significantly improved outcomes for children with hepatic malignancies, including hepatoblastoma and hepatocellular carcinoma. The evolution from extensive resections to parenchymal-sparing procedures has demonstrated superior long-term functional preservation without compromising oncological outcomes. Evidence supports that organ-preserving techniques reduce postoperative morbidity, enhance quality of life, and provide excellent long-term survival rates when applied with appropriate patient selection criteria. Future directions include robotic-assisted surgery, intraoperative imaging guidance, and personalized surgical approaches based on individual tumor biology and patient characteristics.